STRATEGIC CONSIDERATIONS OVERRIDING THE NON-PROLIFERATION PRIORITIES: AN ANALYSIS OF INDO-US CIVIL NUCLEAR DEAL (Margalla Papers, 2023)
The study has reviewed a critical question of how great powers override non-proliferation priorities at times of strategic considerations by creating ease out of their international obligations. In 2008, the Bush Administration entered a strategic understanding with India to enhance cooperation in the nuclear field that paved the way for civilian nuclear trade with New Delhi and carefully crafted the power dynamics favouring India. This study finds out that the so-called ‘Non-proliferation Enhancement Act’ provided an undue advantage to India over Pakistan, thus forcing Islamabad to improve the effectiveness and outreach of her strategic assets to mitigate the apprehensive threshold. Although the nuclearisation of South Asia was implicated in the non-proliferation regime, it ensured strategic balance in the region and shall continue to do so in the national security calculations. The Indo-US nuclear cooperation continues to haunt the dynamics of nuclear parity that concurrently possess serious security implications for Pakistan by allowing India to manipulate the threshold. Therefore, this paper investigates the genesis of the Indo-US deal, the geostrategic and commercial interests of major powers underpinning this deal, implications for Pakistan, steps taken by Pakistan so far and the way forward. The study is deductive and has contested the assumption of the nuclear non-proliferation regime as a theoretical framework. Bibliography EntrySargana, Tauqeer Hussain. 2023. "Strategic Considerations Overriding the Non-Proliferation Priorities: An Analysis of Indo-US Civil Nuclear Deal." Margalla Papers 27 (1): 40-52.